Preparation method and application of all-organic cross-linked polyimide composite insulating material

Through the preparation method of all-organic crosslinked polyimide composite insulating material, the problem of reducing the breakdown field strength of traditional polyimide composite materials in high-temperature electrical systems is solved, and high dielectric constant and high breakdown performance are achieved. Combined, the energy storage density and insulation performance are significantly improved.

CN119463492AInactive Publication Date: 2025-02-18HARBIN UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411539588.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

After the introduction of nano-inorganic fillers, the increase in the dielectric constant of traditional polyimide composite materials leads to a decrease in the breakdown field strength, making it difficult to maintain good insulation performance in high-temperature electrical systems.

Method used

Using the preparation method of all-organic crosslinked polyimide composite insulating material, 2,2'-bis(trifluoromethyl)diaminobiphenyl and hexafluorodianhydride are used in N,N-dimethylacetamide The reaction was performed by adding the crosslinking agent 2,4,6-triaminopyrimidine, and the film was scraped on the substrate by a coating scraper method, and then insulated at 350°C to complete the crosslinking reaction.

Benefits of technology

The dielectric constant and breakdown performance of the polyimide polymer system are improved, the problems of high dielectric constant and high breakdown field strength are decoupled, the energy storage density is significantly increased, and the dielectric loss is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463492A_ABST
    Figure CN119463492A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of an all-organic cross-linked polyimide composite insulating material, and relates to the technical field of polyimide insulation. The invention aims to solve the problem that the breakdown field strength is reduced after a nano inorganic filler is introduced into a traditional composite material taking polyimide as a matrix to increase the dielectric constant. A full-organic system is adopted, the dielectric constant is slightly improved compared with pure polyimide, the breakdown performance is greatly improved, the insulating property of a polyimide polymer system is improved, the problems of high dielectric constant and high breakdown field strength existing in cross-linked polyimide are decoupled, and the dielectric constant and the breakdown field strength are greatly improved. Therefore, the energy storage density of the cross-linked polyimide is obviously increased. The invention can obtain the preparation method and the application of the all-organic cross-linked polyimide composite insulating material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyimide insulation, and in particular to a preparation method and application of a fully organic cross-linked polyimide composite insulation material. Background Art

[0002] With the continuous development of modern electronic and power system technology, polymer film capacitors have increasingly important application value in the field of modern electronic and power systems due to their high breakdown strength. Although people have done a lot of work on improving the breakdown performance of polymer composites, it is still a huge challenge to improve the breakdown performance and dielectric properties of polymer composites under the premise of large-scale industrial production.

[0003] At the same time, researchers have found that polyimide (PI) has good mechanical, chemical and electrical properties in a very wide temperature range, so it has been widely used. Especially in terms of insulating materials, it has been widely used for inter-turn insulation of inverter-powered traction motors and insulation of electronic equipment such as integrated circuits and sensors. However, in high-temperature electrical systems, polymer dielectric materials usually suffer from dielectric loss, which leads to reduced insulation performance of polymer composites. Previous research has mainly focused on doping nano-inorganic fillers. However, there are also problems with significantly increased dielectric loss and conductivity of composite films and reduced breakdown field strength. Summary of the invention

[0004] The purpose of the present invention is to solve the problem that the introduction of nano inorganic fillers into a traditional composite material based on polyimide to increase the dielectric constant will lead to a decrease in breakdown field strength, and to provide a preparation method and application of a fully organic cross-linked polyimide composite insulating material.

[0005] A method for preparing a fully organic cross-linked polyimide composite insulating material is carried out according to the following steps:

[0006] Step S1: preparing a polyimide solution;

[0007] Add 2,2'-bis(trifluoromethyl)diaminobiphenyl to N,N-dimethylacetamide, then add hexafluorodianhydride under stirring, and continue stirring for 12 to 16 hours after the hexafluorodianhydride is completely dissolved to obtain a polyimide solution a;

[0008] Step S2: Preparation of fully organic cross-linked polyimide composite insulation material;

[0009] Add a crosslinking agent 2,4,6-triaminopyrimidine to the polyimide solution a obtained in step S1, and stir until it becomes viscous to obtain a solution b; evacuate the solution b, and then use a film coating scraper to scrape the surface of the pretreated substrate, and then gradually heat the substrate to 350° C. and keep it warm at 350° C. for 60 to 120 minutes; after the insulation is completed, cool to room temperature, peel off the film on the substrate, and obtain a fully organic crosslinked polyimide composite insulating material; the mass fraction of the crosslinking agent 2,4,6-triaminopyrimidine in the polyimide in the polyimide solution a is 0.5%, 1%, 1.5% or 2%.

[0010] An application of a fully organic cross-linked polyimide composite insulating material, and the application of the fully organic cross-linked polyimide composite insulating material in a dielectric capacitor.

[0011] Beneficial effects of the present invention:

[0012] (1) The present invention discloses a method for preparing a fully organic cross-linked polyimide composite insulating material, which comprises first dissolving 2,2'-bis(trifluoromethyl)diaminobiphenyl in N,N-dimethylacetamide, then dissolving hexafluorodianhydride in N,N-dimethylacetamide four times, then adding a cross-linking agent, and then preparing a composite film by a solution casting method. At present, the introduction of nanomaterials with high dielectric constants into a polymer matrix to form a polymer composite material usually results in an increase in dielectric constant at the expense of a decrease in breakdown field strength and mechanical properties. The present invention adopts a fully organic system, the dielectric constant is slightly improved compared to pure polyimide, and the breakdown performance is greatly improved, the insulation performance of the polyimide polymer system is improved, and the problems of high dielectric constant and high breakdown field strength existing in the cross-linked polyimide are decoupled, thereby significantly increasing the energy storage density of the cross-linked polyimide.

[0013] (2) The fully organic cross-linked polyimide composite insulating material prepared by the method of the present invention has excellent dielectric properties and breakdown properties, and has reduced losses, and can be widely used in advanced fields such as electrical, electronic and new energy vehicles.

[0014] (3) The preparation process of the present invention is simple, economical and practical, effectively saves resources, is suitable for large-scale industrial production, and provides a good strategy for developing new application paths for polyimide insulating media.

[0015] The invention can obtain a preparation method and application of a fully organic cross-linked polyimide composite insulating material. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1A DC breakdown Weibull distribution diagram of a fully organic cross-linked polyimide composite insulating material of the present invention is shown, where ■ represents a pure polyimide film, ● represents a cross-linking agent having a mass fraction of 0.5%, ▲ represents a cross-linking agent having a mass fraction of 1.0%, ▼ represents a cross-linking agent having a mass fraction of 1.5%, and ◆ represents a cross-linking agent having a mass fraction of 2.0%;

[0017] Figure 2 The Fourier transform infrared spectrum of a fully organic cross-linked polyimide composite insulating material of the present invention is shown, where a represents a pure polyimide film, b represents a cross-linking agent having a mass fraction of 0.5%, c represents a cross-linking agent having a mass fraction of 1.0%, d represents a cross-linking agent having a mass fraction of 1.5%, and e represents a cross-linking agent having a mass fraction of 2.0%;

[0018] Figure 3 Indicates the dielectric constant test result of a fully organic cross-linked polyimide composite insulating material of the present invention, ■ indicates a pure polyimide film, ● indicates that the mass fraction of the cross-linking agent is 0.5%, ▲ indicates that the mass fraction of the cross-linking agent is 1.0%, ▼ indicates that the mass fraction of the cross-linking agent is 1.5%, and ◆ indicates that the mass fraction of the cross-linking agent is 2.0%;

[0019] Figure 4 Indicates the dielectric loss test results of a fully organic cross-linked polyimide composite insulating material of the present invention, ■ indicates a pure polyimide film, ● indicates that the mass fraction of the cross-linking agent is 0.5%, ▲ indicates that the mass fraction of the cross-linking agent is 1.0%, ▼ indicates that the mass fraction of the cross-linking agent is 1.5%, and ◆ indicates that the mass fraction of the cross-linking agent is 2.0%;

[0020] Figure 5 The conductivity test results of the fully organic cross-linked polyimide composite insulating material of the present invention are shown, ■ represents pure polyimide film, ● represents 0.5% by mass fraction of the cross-linking agent, ▲ represents 1.0% by mass fraction of the cross-linking agent, ▼ represents 1.5% by mass fraction of the cross-linking agent, and ◆ represents 2.0% by mass fraction of the cross-linking agent. DETAILED DESCRIPTION

[0021] Specific implementation method 1: This implementation method is a method for preparing a fully organic cross-linked polyimide composite insulating material, which is carried out according to the following steps:

[0022] Step S1: preparing a polyimide solution;

[0023] Add 2,2'-bis(trifluoromethyl)diaminobiphenyl to N,N-dimethylacetamide, then add hexafluorodianhydride under stirring, and continue stirring for 12 to 16 hours after the hexafluorodianhydride is completely dissolved to obtain a polyimide solution a;

[0024] Step S2: Preparation of fully organic cross-linked polyimide composite insulation material;

[0025] Add a crosslinking agent 2,4,6-triaminopyrimidine to the polyimide solution a obtained in step S1, and stir until it becomes viscous to obtain a solution b; evacuate the solution b, and then use a film coating scraper to scrape the surface of the pretreated substrate, and then gradually heat the substrate to 350° C. and keep it warm at 350° C. for 60 to 120 minutes; after the insulation is completed, cool to room temperature, peel off the film on the substrate, and obtain a fully organic crosslinked polyimide composite insulating material; the mass fraction of the crosslinking agent 2,4,6-triaminopyrimidine in the polyimide in the polyimide solution a is 0.5%, 1%, 1.5% or 2%.

[0026] Specific embodiment 2: The difference between this embodiment and specific embodiment 1 is that the ratio of the mass of 2,2'-bis(trifluoromethyl)diaminobiphenyl, the volume of N,N-dimethylacetamide and the mass of hexafluorodianhydride is (2.3-3.4) g: (19-20) mL: (2.9-3.4) g.

[0027] The other steps are the same as those in the first specific implementation.

[0028] Specific implementation method three: The difference between this implementation method and specific implementation method one or two is that the stirring speed in step S1 is 50-100 rpm.

[0029] The other steps are the same as those in the first or second embodiment.

[0030] Specific embodiment 4: The difference between this embodiment and specific embodiments 1 to 3 is that in step S1, hexafluorodianhydride is added in four times, the first time adding 1 / 2 of the total mass, the second time adding 1 / 4 of the total mass, and the third and fourth times both adding 1 / 8 of the total mass.

[0031] The other steps are the same as those in Specific Embodiments 1 to 3.

[0032] Specific embodiment 5: The difference between this embodiment and specific embodiments 1 to 4 is that the stirring speed in step S2 is 100-150 rpm.

[0033] The other steps are the same as those in Specific Embodiments 1 to 4.

[0034] Specific implementation method 6: The difference between this implementation method and specific implementation methods 1 to 5 is that the vacuuming time in step S2 is 7 to 8 hours.

[0035] The other steps are the same as those in Specific Embodiments 1 to 5.

[0036] Specific embodiment seven: The difference between this embodiment and any one of specific embodiments one to six is ​​that the pretreated substrate described in step S2 is processed according to the following steps: first, the substrate is cleaned with clean water for 1 to 3 times, then wiped clean with dust-free paper, and then cleaned with anhydrous ethanol for 3 to 5 times, and finally dried at 50°C to 60°C for 1 to 2 hours to obtain a pretreated substrate, which is a high temperature resistant glass plate.

[0037] The other steps are the same as those in Specific Embodiments 1 to 6.

[0038] Specific implementation eight: The difference between this implementation and specific implementations one to seven is that: after the insulation in step S2 is completed, the substrate is first placed for 8 to 9 hours for natural cooling, and then the substrate is placed in ice water at -5℃ to -10℃ for cooling; in step S2, the substrate is first soaked in hot water at 95℃ to 100℃ for 10 to 15 minutes, and then the film on the substrate is peeled off.

[0039] The other steps are the same as those in Specific Embodiments 1 to 7.

[0040] Specific embodiment nine: The difference between this embodiment and specific embodiments one to eight is that the gradient heating in step S2 is to heat the substrate from 80°C to 110°C, 140°C, 170°C, 200°C, 230°C, 260°C, 290°C, 320°C and 350°C in sequence, and the insulation time at 80°C is 6h, and the insulation time at 110°C, 140°C, 170°C, 200°C, 230°C, 260°C, 290°C and 320°C is 0.5h.

[0041] The other steps are the same as those in Specific Embodiments 1 to 8.

[0042] Specific implementation method ten: This implementation method is an application of a fully organic cross-linked polyimide composite insulating material, and the application of the fully organic cross-linked polyimide composite insulating material in a dielectric capacitor.

[0043] The following examples are used to verify the beneficial effects of the present invention:

[0044] Embodiment 1: A method for preparing a fully organic cross-linked polyimide composite insulating material is carried out according to the following steps:

[0045] Step S1: preparing a polyimide solution;

[0046] In a three-necked flask, 2.355 g of 2,2'-bis(trifluoromethyl)diaminobiphenyl was dissolved in 20 mL of N,N-dimethylacetamide, and then 3.3318 g of hexafluorodianhydride was added in four portions at a stirring speed of 50 rpm, with 1 / 2 of the total mass added in the first portion, 1 / 4 of the total mass added in the second portion, and 1 / 8 of the total mass added in the third and fourth portions; after the hexafluorodianhydride was completely dissolved, stirring was continued for 12 h to obtain a uniform and viscous polyimide solution a;

[0047] Step S2: Preparation of fully organic cross-linked polyimide composite insulation material;

[0048] First, prepare a high temperature resistant glass plate with a size of 200 mm × 16 mm × 4 mm, wash the high temperature resistant glass plate with clean water for 3 times, then wipe it with dust-free paper, then wash it with anhydrous ethanol for 3 times, and finally dry it at 55 ° C for 1 hour to obtain a pretreated high temperature resistant glass plate;

[0049] Add a crosslinking agent 2,4,6-triaminopyrimidine to the polyimide solution a obtained in step S1, and stir at a stirring speed of 100 rpm until it becomes viscous to obtain a solution b; evacuate the solution b for 7 hours, and then use a film coating scraper to scrape the surface of the pretreated high-temperature resistant glass plate, and then put the glass plate into an oven and gradually increase the temperature from the starting temperature of 80°C to 350°C, and keep it warm at 350°C for 120 minutes; after the insulation is completed, place it for 8 hours for natural cooling, and then put the substrate into -7°C ice water to cool to room temperature, peel off the film on the glass plate and store it well, to obtain a fully organic cross-linked polyimide composite insulating material; the mass fraction of the crosslinking agent 2,4,6-triaminopyrimidine in the polyimide in the polyimide solution a is 0.5%.

[0050] The cross-linking agent 2,4,6-triaminopyrimidine was purchased from Aladdin Reagent Company.

[0051] Example 2: In this example, the mass fraction of the crosslinking agent 2,4,6-triaminopyrimidine in the polyimide solution a is 1%; other experimental conditions are the same as those in Example 1.

[0052] Example 3: In this example, the mass fraction of the cross-linking agent 2,4,6-triaminopyrimidine in the polyimide solution a is 1.5%; other experimental conditions are the same as those in Example 1.

[0053] Example 4: In this example, the mass fraction of the crosslinking agent 2,4,6-triaminopyrimidine in the polyimide solution a is 2%; other experimental conditions are the same as those in Example 1.

[0054] Comparative Example 1: In this comparative example, no crosslinking agent is added in step S2, that is, a pure polyimide film is prepared; other experimental conditions are the same as those in Example 1.

[0055] Figure 1 The DC breakdown Weibull distribution diagram of the all-organic cross-linked polyimide composite insulating material of the present invention is shown, where ■ represents a pure polyimide film, ● represents a cross-linking agent having a mass fraction of 0.5%, ▲ represents a cross-linking agent having a mass fraction of 1.0%, ▼ represents a cross-linking agent having a mass fraction of 1.5%, and ◆ represents a cross-linking agent having a mass fraction of 2.0%; Figure 1 As shown in the figure, with the increase of the mass fraction of the cross-linking agent, the breakdown field strength first increases and then decreases. The breakdown field strength of pure polyimide is 520kV / mm. When the mass fraction of the cross-linking agent is 1.0%, the breakdown field strength reaches a maximum value of 660kV / mm, which is 26% higher than that of pure polyimide. With the addition of the cross-linking agent, the movement of carriers inside the composite material is restricted, which greatly increases the breakdown field strength.

[0056] Figure 2 The Fourier transform infrared spectrum of a fully organic cross-linked polyimide composite insulating material of the present invention is shown, where a represents a pure polyimide film, b represents a cross-linking agent having a mass fraction of 0.5%, c represents a cross-linking agent having a mass fraction of 1.0%, d represents a cross-linking agent having a mass fraction of 1.5%, and e represents a cross-linking agent having a mass fraction of 2.0%; Figure 2 As shown in the figure, with the addition of the crosslinking agent, the crosslinked polyimide has a -1 A peak appears at the wavelength, which indicates that the amino group in the cross-linker reacts with the carboxyl group in the PAA acid.

[0057] Figure 3 : represents the dielectric constant test result of a fully organic cross-linked polyimide composite insulating material of the present invention, ■ represents a pure polyimide film, ● represents a cross-linking agent with a mass fraction of 0.5%, ▲ represents a cross-linking agent with a mass fraction of 1.0%, ▼ represents a cross-linking agent with a mass fraction of 1.5%, and ◆ represents a cross-linking agent with a mass fraction of 2.0%; Figure 3 As shown in the figure, with the increase of the mass fraction of the cross-linking agent, the dielectric constant has a trend of continuously decreasing compared with pure polyimide. When the mass fraction of the cross-linking agent is 1%, the dielectric constant is the lowest at 2.9.

[0058] Figure 4 : represents the dielectric loss test result of a fully organic cross-linked polyimide composite insulating material of the present invention, ■ represents a pure polyimide film, ● represents a cross-linking agent with a mass fraction of 0.5%, ▲ represents a cross-linking agent with a mass fraction of 1.0%, ▼ represents a cross-linking agent with a mass fraction of 1.5%, and ◆ represents a cross-linking agent with a mass fraction of 2.0%; Figure 4 As shown, the fully organic cross-linked polyimide composite insulation material is 3 Hz are all below 0.006.

[0059] Figure 5 : represents the conductivity test result of a fully organic cross-linked polyimide composite insulating material of the present invention, ■ represents a pure polyimide film, ● represents a cross-linking agent with a mass fraction of 0.5%, ▲ represents a cross-linking agent with a mass fraction of 1.0%, ▼ represents a cross-linking agent with a mass fraction of 1.5%, and ◆ represents a cross-linking agent with a mass fraction of 2.0%; Figure 5 As shown, it can be seen that in 10 0 Hz~10 2 In the frequency range of Hz, the conductivity of the composite material is lower than that of pure polyimide.

Claims

1. A method for preparing a fully organic cross-linked polyimide composite insulating material, characterized in that The preparation method is carried out according to the following steps: Step S1: preparing a polyimide solution; Add 2,2'-bis(trifluoromethyl)diaminobiphenyl to N,N-dimethylacetamide, then add hexafluorodianhydride under stirring, and continue stirring for 12 to 16 hours after the hexafluorodianhydride is completely dissolved to obtain a polyimide solution a; Step S2: Preparation of fully organic cross-linked polyimide composite insulation material; Add a crosslinking agent 2,4,6-triaminopyrimidine to the polyimide solution a obtained in step S1, and stir until it becomes viscous to obtain a solution b; evacuate the solution b, and then use a film coating scraper to scrape the surface of the pretreated substrate, and then gradually heat the substrate to 350° C. and keep it warm at 350° C. for 60 to 120 minutes; after the insulation is completed, cool to room temperature, peel off the film on the substrate, and obtain a fully organic crosslinked polyimide composite insulating material; the mass fraction of the crosslinking agent 2,4,6-triaminopyrimidine in the polyimide in the polyimide solution a is 0.5%, 1%, 1.5% or 2%.

2. The method for preparing a fully organic cross-linked polyimide composite insulating material according to claim 1, characterized in that The ratio of the mass of 2,2'-bis(trifluoromethyl)diaminobiphenyl, the volume of N,N-dimethylacetamide and the mass of hexafluorodianhydride is (2.3-3.4) g: (19-20) mL: (2.9-3.4) g.

3. The method for preparing a fully organic cross-linked polyimide composite insulating material according to claim 1, characterized in that The stirring speed in step S1 is 50 to 100 rpm.

4. The method for preparing a fully organic cross-linked polyimide composite insulating material according to claim 1, characterized in that In step S1, hexafluorodianhydride is added in four times, 1 / 2 of the total mass is added in the first time, 1 / 4 of the total mass is added in the second time, and 1 / 8 of the total mass is added in the third and fourth times.

5. The method for preparing a fully organic cross-linked polyimide composite insulating material according to claim 1, characterized in that The stirring speed in step S2 is 100 to 150 rpm.

6. The method for preparing a fully organic cross-linked polyimide composite insulating material according to claim 1, characterized in that The vacuuming time in step S2 is 7 to 8 hours.

7. The method for preparing a fully organic cross-linked polyimide composite insulating material according to claim 1, characterized in that The pretreated substrate described in step S2 is processed according to the following steps: first, the substrate is cleaned with clean water for 1 to 3 times, then wiped clean with dust-free paper, then cleaned with anhydrous ethanol for 3 to 5 times, and finally dried at 50°C to 60°C for 1 to 2 hours to obtain a pretreated substrate, wherein the substrate is a high temperature resistant glass plate.

8. The method for preparing a fully organic cross-linked polyimide composite insulating material according to claim 1, characterized in that After the heat preservation in step S2 is completed, the substrate is first placed for 8 to 9 hours for natural cooling, and then the substrate is placed in ice water at -5°C to -10°C for cooling; in step S2, the substrate is first soaked in hot water at 95°C to 100°C for 10 to 15 minutes, and then the film on the substrate is peeled off.

9. The method for preparing a fully organic cross-linked polyimide composite insulating material according to claim 1, characterized in that In step S2, the gradient heating is to heat the substrate from 80°C to 110°C, 140°C, 170°C, 200°C, 230°C, 260°C, 290°C, 320°C and 350°C in sequence, and the holding time at 80°C is 6 hours, and the holding time at 110°C, 140°C, 170°C, 200°C, 230°C, 260°C, 290°C and 320°C is 0.5 hours.

10. Use of a fully organic cross-linked polyimide composite insulating material prepared by the method according to any one of claims 1 to 9, characterized in that The application of the fully organic cross-linked polyimide composite insulating material in dielectric capacitors.

Citation Information

Patent Citations

  • Cross-linked polyimide insulating dielectric film as well as preparation method and application thereof

    CN117801274A